Improved secondary control for optimal total harmonic distortion compensation of parallel connected DGs in islanded microgrids. Issue 1 (24th January 2019) - Andishgar, Mohammad Hadi; Gholipour, Eskandar; Hooshmand, Rahmat‐Allah
Abstract : This study proposes a two‐layer hierarchical control to actualize optimal total harmonic distortion (THD) compensation in different buses of parallel‐connected inverters in islanded microgrids which had not been studied so far. The proposed secondary layer is used to realize THD compensation of sensitive load bus (SLB) and make distributed generators (DGs) distribute the compensating efforts between them according to their rated capacity. It is noteworthy that improving THD at the SLB can lead to an increase in THD at local buses and/or DG terminals. Although the THD limitations of these buses are not as strict as the THD limitation of SLB, it is necessary to control them within their allowed range. This important problem is not well studied in the literature. A novel complementary part is designed and added to the secondary control to tune the compensation portion of each DG while the THD limitations in DG terminals and local buses are considered. The proposed method actualizes a multi‐level voltage quality control in multi‐bus islanded microgrids with parallel DGs through a simple yet effective solution. Furthermore, considering the DGs peak current limitation is added to the controller and a method for calculating this peak value is proposed.